Tourism and development concepts and issues - Sharpley Richard; Telfer David J (New Delhi Viva Books, 2006)
This text explores the role of tourism as a potential contibutor to socio-economic development in destination areas. Establishing a link between tourism studies and development studies, it considers what is meant by development, the processes through
Keywords: Tourism